2006
DOI: 10.1021/jp062575+
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Analysis. 24. Structure and Composition of Gaseous Oxalyl Fluoride, C2F2O2:  Electron-Diffraction Investigation Augmented by Data from Microwave Spectroscopy and Molecular Orbital Calculations

Abstract: The molecular structure and composition of gaseous oxalyl fluoride (OXF) has been investigated by electron diffraction (GED) at nozzle-tip temperatures of -10, 149, and 219 degrees C. The GED data were augmented by molecular orbital calculations, and the analysis was aided by use of rotational constants from microwave (MW) spectroscopy. As in the other oxalyl halides, there are two stable species, of which the more stable is periplanar anti (i.e., trans). However, unlike these other halides in which the second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
18
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 21 publications
(28 reference statements)
6
18
0
Order By: Relevance
“…Nine excited states of the torsional fundamental mode were assigned and the torsional fundamental was determined to be 26(5) cm À1 . The results of the recent electron diffraction investigation by Friesen et al [15] confirmed the geometry of (COF) 2 to be a mixture of trans and cis conformers. The electron diffraction [15], microwave (absolute intensities measurements) [14], and vibrational spectroscopy [12,13,16] investigations of (COF) 2 all determined the conformer energy (enthalpy) difference in the gas phase to be 230-400 cm À1 ; the fraction of (COF) 2 molecules in the cis conformer at room temperature is hence significant.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Nine excited states of the torsional fundamental mode were assigned and the torsional fundamental was determined to be 26(5) cm À1 . The results of the recent electron diffraction investigation by Friesen et al [15] confirmed the geometry of (COF) 2 to be a mixture of trans and cis conformers. The electron diffraction [15], microwave (absolute intensities measurements) [14], and vibrational spectroscopy [12,13,16] investigations of (COF) 2 all determined the conformer energy (enthalpy) difference in the gas phase to be 230-400 cm À1 ; the fraction of (COF) 2 molecules in the cis conformer at room temperature is hence significant.…”
Section: Introductionmentioning
confidence: 82%
“…The electron diffraction [15], microwave (absolute intensities measurements) [14], and vibrational spectroscopy [12,13,16] investigations of (COF) 2 all determined the conformer energy (enthalpy) difference in the gas phase to be 230-400 cm À1 ; the fraction of (COF) 2 molecules in the cis conformer at room temperature is hence significant. This conclusion was supported by theoretical calculations [12][13][14][15][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…However, no data on the structure of the second conformers of oxalyl halides in excited electronic states are available. Earlier, only transitions of the trans-conformers were observed in the vibronic absorption spectra of oxalyl halides [14,16,[18][19][20], although according to vibrational spectroscopy and electron diffraction studies, the values of conformer energy (enthalpy) differences of oxalyl halides in the ground electronic state in the gas phase were relatively small, and the content of the second conformers was rather high [2,[4][5][6][9][10][11]22].…”
Section: Introductionmentioning
confidence: 96%
“…It was proven experimentally that all molecules investigated in the vapor phase have two conformers in the ground electronic state: the planar trans-conformer (dOCCO = 180°, C 2h symmetry), which is lower in energy [1][2][3][4][5][6], and the second conformer-planar cis (dOCCO = 0°, C 2v symmetry) for glyoxal (COH) 2 [7] and oxalyl fluoride (COF) 2 [8,9] or non-planar gauche-conformer (dOCCO > 0°, C 2 symmetry) for oxalyl chloride (COCl) 2 [10] and oxalyl bromide (COBr) 2 [11].…”
Section: Introductionmentioning
confidence: 99%
“…For oxalyl chloridefluoride, there are no experimental data on geometries of conformers in the ground electronic state. The comparison of calculated values could be made only with geometric parameters of oxalyl fluoride (COF) 2 and oxalyl chloride (COCl) 2 obtained experimentally [29,30] or theoretically [2,3]. In general, if the CCSD(T)/ cc-pVTZ or cc-pVQZ values are compared, the respective geometric parameters of CFO, CClO fragments of COCl-COF, (COF) 2 , and (COCl) 2 molecules are very similar.…”
Section: Geometric Parametersmentioning
confidence: 99%